HUBUNGAN PENGETAHUAN IBU POSTPARTUM TENTANG KOLOSTRUM TERHADAP PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR DI RUANG CAMAR 1 RSUD ARIFIN ACHMAD PEKANBARU - Sari, Endah Purwani (Jurnal Martenity and Neonatal, 2019)
Colostrum is the fluid that was first secreted by the breast glands. Colostrum contains white blood cells and antibodies that are higher than actual breast milk, especially the content of immunoglobulin A that helps to coat the baby's gut that is still vulnerable and prevent germs from entering the baby. The purpose of this research is to know the relation of knowledge of postpartum mother about colostrum to giving colostrum to newborn baby in gull room 1 RSUD Arifin Achmad Pekanbaru year 2018. This research type is quantitative research with analytical method with cross sectional research design. Population in this research is All Postpartum Mother in Gamar 1 RSUD Arifin Achmad Pekanbaru With amount in the last 3 month counted 420 people and average per month as many as 140 people. Samples on is postpartum mother residing in seagull room 1 RSUD Arifin Achmad at period of research. the sample in this research using the minimum sample is 30 samples by using the technique of Accidental Sampling. The instrument used in this research is a questionnaire. Analysis in this research is univariate and bivariate analysis. The result of univariate research shows that from 30 respondents, 17 respondents (56.67%) have less knowledge and 13 respondents (43,33%) have good knowledge. The result of bivariate analysis showed that from all respondents that amounted to 30 people obtained respondents with less knowledge as much as 17 respondents with no colostrum as much as 14 respondents and respondents with good knowledge as much as 13 respondents with no colostrum as much as 3 respondents from Chi square test results obtained P value 0,002 where P value â‰¤ 0,05 Ho is rejected meaning significant or existence of meaningful relation.